2009
DOI: 10.4055/cios.2009.1.3.128
|View full text |Cite
|
Sign up to set email alerts
|

Bony Landmarks for Determining the Mechanical Axis of the Femur in the Sagittal Plane during Total Knee Arthroplasty

Abstract: BackgroundThere is no accepted landmark for the mechanical axis of the femoral axis in sagittal plane in conventional total knee arthroplasty.MethodsAs palpable anatomic landmarks of the femur, lateral epicondyle, and anterior margin of the greater trochanter were identified. The line connecting these two landmarks was defined as the "palpable sagittal axis". The mechanical axis of the femur was compared with the palpable sagittal axis and the distal femoral anterior cortex axis. These axes were also compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 13 publications
1
33
0
Order By: Relevance
“…We are cognizant of the distal femoral anterior cortex being 4.1 degrees flexed in the sagittal axis. 22 According to the mathematical formula of using 2 circular arcs to describe the femoral condyles, 12 the largest fitting ellipse was superimposed on the femoral condyles. Using this approach, the posterior angulation is 99.8 degrees with SD of 4.9 degrees.…”
Section: Discussionmentioning
confidence: 99%
“…We are cognizant of the distal femoral anterior cortex being 4.1 degrees flexed in the sagittal axis. 22 According to the mathematical formula of using 2 circular arcs to describe the femoral condyles, 12 the largest fitting ellipse was superimposed on the femoral condyles. Using this approach, the posterior angulation is 99.8 degrees with SD of 4.9 degrees.…”
Section: Discussionmentioning
confidence: 99%
“…1). First, following Seo et al [21], we aligned the mechanical axis of the femur on the sagittal plane. The mechanical axis was defined as the line connecting the center of the femoral head to the apex point of the intercondylar notch.…”
Section: Methodsmentioning
confidence: 99%
“…This statement confirms other studies. Seo et al [8] observed a mean 4°dif-ference between the mechanical axis and distal cortical axis of the femur. Chung et al [3] observed that differences ranged between 0°and 4°between four different axes.…”
Section: Discussionmentioning
confidence: 98%